Gliomas - Berger, Mitchel S.; Weller, Michael, 1962- (Handbook of clinical neurology ;, 2016)
Researchers' knowledge of gliomas continues to advance rapidly at both the basic and translational levels, and Gliomas provides a thorough overview of the evolving fields of tumor biology and clinical medicine as they relate to our understanding of brain tumors. Gliomas reviews the current paradigms that underlie these fields, beginning with the molecular epidemiology of glioma susceptibility and prognosis through population-based science and genome-wide association studies. The book's discussion of imaging modalities extends beyond advances in anatomical imaging to include metabolic and physiological studies. This work provides thorough discussion of the clinical view of tumors, ranging from the presentation of the patient to surgical management, and covers all therapeutic options for patient care, including chemotherapy, targeted molecular therapies, immunotherapies, and even personalized approaches to impact the set of lesions. Additionally, the book discusses radiotherapy with regard to the many options available to treat patients using myriad fractionated techniques with various sources. Finally, Gliomas reviews issues specific to the quality of life for patients, and techniques for maximizing the effect of caregivers. Edited and authored by premier researchers from around the world, Gliomas is a comprehensive reference for clinicians and researchers seeking the most up-to-date information on gliomas, and a guide to the best ways to effectively manage glioma patients and their care. Synthesizes widely dispersed information on the management of gliomas into one comprehensive resource Chapters written by international authors who are preeminent researchers in the field Fully explores the therapeutic options for patient care, from chemotherapy to radiotherapy to personalized approaches.